The radical behaviorism and the psychology as science (Brazilian Journal of Behavioral and Cognitive Therapy, 2005)
The understanding of B. F. Skinner's approach to Psychology can be considered as a good beginning for the comprehension of radical behaviorism current characteristics. The present paper details Skinner's analysis in three publications where he seems to choose to present aspects of his system by confronting his assertions with other ones already exiting, and generally accepted, in Psychology. The aim here is to follow through part of Skinner's writing, analyzing the main oppositions argued by Skinner in the following publications: The Operational analysis of psychological terms (1945), Behaviorism at fifty (1963), and About behaviorism (1974) first chapter mainly. As a result, the theme of choice, Skinner's arguments, and the corresponding main contraposition guiding Skinner's exposition are identified and discussed in each one of these manuscripts. In the central issue argued by Skinner is the method of choice to be adopted in Psychology studies, in Psychology's subject matter is the central question tackled by Skinner, and, finally, in A the causal mode that should underlie and guide the study of Psychology's subject matter and Psychology's selection of methods is the topic of choice.
Keywords: radical behaviorism; B. F. Skinner; subject matter of Psychology; methods of Psychology; causal model